FUN ACTIVITIES TO TEACH VOCABULARY FOR YOUNG LEARNERS: A LIBRARY RESEARCH - Ni Luh Sri Wahyu Purnami (E-LINK JOURNAL, 2022)
It is found that young learners in Indonesia still have low vocabulary mastery. It is resulted from the teacher factors in teaching vocabulary which cannot use appropriate media and technique. This study investigates kinds of fun activities under young learners' characteristics and learning styles to teach vocabulary. Based on library research, teachers can implement nine kinds of fun activities: singing/listening to a song, watching videos, playing games, listening to a story/storytelling, conversational activity, study tour/outdoors, coloring, and using pictures and flashcards. Those activities already meet the characteristics and the learning styles of young learners. However, the teacher must be creative, imaginative, and innovative to implement the activities to make the teaching and learning vocabulary process more enjoyable. Keywords: Vocabulary, young learners, fun activities